Estudo da exploração mineral de areia a partir de geoprocessamento em Feira de Santana - BA (2008 – 2015) - Santos, Adson dos (2019)
The demand for sand in the municipality of Feira de Santana grew from 2002, due to the increase in urban expansion, following the expansion of this in Feira de Santana, between 2000 and 2005, there was a growth of 162% over the period between 1995 and 2000, becoming a great vector of economic growth in Brazil, and with that its consequences become more and more visible. The municipality of Feira de Santana - BA, the second largest city in the state, could not be immune to this phenomenon. With the increasing urban development the civil construction has been emphasizing. With this, the mineral extraction of sand becomes indispensable. However, with this extraction occur the environmental impacts from this action. This work has the purpose of proving the environmental and social degradation provoked by the extraction of sand and the lack of inspection by the municipal public power. This work was developed with the construction of physical thematic maps through geoprocessing and visits to the extraction sites where an analysis of the data was made. The methodology used in this work was efficient for the mapping and analysis of the spatial configuration of the areas of mineral extraction of sand in Feira de Santana. Geotechnology tools were of fundamental importance for data organization as well as for the construction of integrated space environments. From the modeling used we concluded that the exploited areas have medium to high level of environmental degradation, due to the size exploited and the magnitude of these projects. With this, it was concluded that the impacts caused by the extraction are evident and the competent agencies cannot supervise the sites. Miners, for their part, do not fulfill their role of reclaiming the areas they have degraded, and continue to impact the local environment. Field visits and sand registration, coupled with informal conversations with sand chambers (people carrying the ore), lead us to believe. That being said, the inefficiency of the inspections becomes a stimulus to the illegal practices of the enterprises. It is necessary to encourage further research related to this topic of study, in order to improve qualitative and quantitative assessments on clandestine mineral extraction enterprises in Feira de Santana, it is suggested still the study of potential exploration areas based on the experience obtained at the end of this work.